Occurrence, genetic diversity, and antimicrobial resistance of methicillin-resistant Staphylococcus spp. in hospitalized and non-hospitalized cats in Brazil. - Thayanne Gabryelle Viana de Souza; Jordana Almeida Santana; Marina Mourão Sena Claudino; Silvia Trindade Pereira; Rafael Gariglio Clark Xavier; Victor Santos do Amarante; Yasmin Gonçalves de Castro; Elaine Maria Seles Dorneles; Flavia Figueira Aburjaile; Vasco Ariston de Carvalho; Bertram Brenig; Rodrigo Otávio Silveira Silva (PLoS ONE, 2024)
Methicillin-resistant Staphylococci (MRS) cause infections at various sites and exhibit multidrug resistance. Despite their importance in veterinary medicine, only little is known about Staphylococcus spp. colonizing and infecting cats. Therefore, in this study, we aimed to isolate and identify Staphylococcus spp. colonizing hospitalized and non-hospitalized domestic cats and analyze their antimicrobial resistance profiles, genetic diversity, and risk factors associated with MRS colonization. A total of 218 oral and axillary swabs were obtained from 109 cats, including 77 non-hospitalized and 32 hospitalized cats. After plating on selective media, the isolates were identified via matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and rpoB and 16S rRNA gene sequencing. Subsequently, antimicrobial sensitivity of the strains was assessed, and they were screened for mecA gene. Methicillin-resistant S. haemolyticus (MRSH) isolates were subjected to multilocus sequence typing, whereas methicillin-resistant S. pseudintermedius (MRSP) and S. felis isolates were subjected to whole genome sequencing. S. felis was most commonly isolated from non-hospitalized cats (28.1%), whereas S. pseudintermedius and MRS were commonly isolated from hospitalized cats (25%). MRSH isolates from hospitalized animals were classified as ST3. The identified MRSP strains belonged to two well-known sequence types, ST551 and ST71. Moreover, antimicrobial use (p = 0.0001), hospitalization (p = 0.0141), and comorbidities (p = 0.002) were associated with increased MRS prevalence in cats.